The validity of the classical patterns of coverage of natural disasters in the Internet Age - García de Torres, Elvira (2012)
This article presents the results of a comparative analysis of the Press coverage of natural disasters in the world by Spanish newspapers during the years 2009 and 2010 and some prominent indicators of social interest in the Internet. The main goals of this exploratory research are to find out if the classic news values shape altogether the agenda of the mainstream newspapers and the citizens and if the cahier de doléances in this specialized field are also in effect in the Internet age.